Promising management strategies to improve crop sustainability and to amend soil salinity - Mishra, Ajay Kumar; Das, Rajeswari; George Kerry, Rout; Biswal, Bisworanjita; Sinha, Trisha; Sharma, Sheetal; Arora, Pooja; Kumar, Mukesh (Frontiers in Environmental Science, 2023)
By affecting 10 percent of the world's total arable land, soil salinity has become a potential threat to feeding the exploding population. As per the current scenario, among 1125 million hectares of salt-affected lands, nearly 76 million hectares are seriously concerned due to human-induced salinization. Due to soil salinization, crop productivity is being hampered. In order to enhance productivity, there is an urgent need to shift the gear from traditional methods to advance 3E (Efficient, Economic and Environmentally sound) technology for soil salinity reclamation and management for better soil health and sustainable crop production. The details mechanism of salt interference with various pathways involved in plant growth and development needs to be understood. This study captures the mechanism of harmful salt interference with nutrient dynamics in soil and various physiological pathways involved in crop growth and yields to apply various soil-oriented (crop residue management, biochar application, agroforestry system) and plant-oriented (PGPM, plant growth regulators, nanotechnology) advanced reclamations and rehabilitation approaches to mitigate its hazardous effect on soil salinity. Monitoring and assessment of salt-affected soils through remote sensing (RS) and geographical information systems (GIS) are pivotal in the management and framing of long-term policies to confront alarming threats to crop productivity and sustainability. This study is an insight into recent developments in soil salinity management and proposes futuristic solutions that could ameliorate soil salinity to attain crop sustainability under adverse environmental conditions.